Beneath the Shadow of the Cross: A Rahnerian Rejoinder to Jean-Luc Marion - Duns, Ryan G. (Philosophy & theology, 2016)
Building on Peter Fritz’s work, this essay contributes to the dialogue between Jean-Luc Marion and Karl Rahner. Often assumed to be incompatible, I argue that there are sufficient points of contact to merit a consideration of how each conceives the relationship between philosophy and theology. Drawing on Hearer of the Word, my Rahnerian rejoinder challenges Marion to be more explicit about the role faith plays in his phenomenology. Ultimately, their work does not fit readily into philosophy or theology, allowing me to suggest that they are better understood as mystagogical thinkers who draw us more deeply into God’s Infinite Mystery.